Superior corrosion protection and in vitro biocompatibility of Na-HAp/CS composite coating on PoPD-coated 316L SS. (December 2018) - Prem Ananth, K.; Sun, Jinxing; Bai, Jiaming
Abstract: The synthesis and development of sodium (Na)-substituted hydroxyapatite (HAp)/chitosan (CS) composite using poly (O-phenylenediamine) (PoPD) coating on 316L SS substrate for improving bioactivity and corrosion protection was studied. The surface of Na-HAp/CS/PoPD bilayer coatings on 316L SS substrate was characterized by diverse analytical techniques. The open circuit potential (OCP) measurement, potentiodynamic polarization, and impedance test revealed that the bilayer coating provides excellent protection to the substrate against the corrosion in the simulated body fluid (SBF) solution. This interior layer of the coating acts as a barrier against the release of metal ions from the substrate, which was confirmed by inductively coupled plasma-atomic emission spectroscopy. Besides, the mechanical properties of the coatings were analyzed. From the obtained results, the bilayer coating exhibited greater mechanical strength than the individual coating. An in vitro bioactivity of the coatings was assessed by immersion in the SBF solution at 7–28 days. The apatite formation of bilayer coatings on 316L SS substrate is found to be more bioactive compared with the Na-HAp, PoPD, and Na-HAp/CS. The in vitro biocompatibility test showed no adverse effects, which was proved by the enhanced biocompatibility of the bilayer coating on 316L SS. Graphical abstract: Highlights: PoPD coating on 316L SS substrate as a first layer by electrodeposition coating method. The POPD coating was excellent barrier against the corrosion protection in SBF solution Na-HAp/CS bilayer coating demonstrate superior mechanical strength and better bioactive than individual coating Bioactive nature of Na-HAp/CS as a bilayer coating on POPD coated 316L SS by electrophoretic technique In vitro test exposed that Na-HAp/PoPD bilayer coating promotes admirable anti corrosive performance and exhibited better cell attachment.